Crossbreeding effects on rabbit reproduction from four maternal lines of rabbits. (7th January 2016) - Ragab, M.; Sánchez, J. P.; Mínguez, C.; Baselga, M.
Abstract : Litter size is essential for an efficient production of rabbit meat. A diallel cross between four maternal lines was carried out and the analysis of the components of litter size has been already done. This paper presents the analysis of litter size traits themselves (total born (TB), number born alive (NBA), number weaned (NW)) and kindling interval (KI), that complete the analysis of the reproductive performance. The 16 genetic groups were distributed in four Spanish farms. The V line was present in all farms in order to be used as reference group. A total of 34 546 parities from 7111 does, were analysed. The crossbreeding parameters were estimated according to Dickerson model. The differences between lines performance were of low magnitude and not significant for litter size traits. The LP line showed the shortest KI followed by H respect to lines A and V. These differences reflected the differences between direct and maternal genetic effects. The differences between the average of all crosses and line V were found to be significant and seemed to be important, being 0.46 for TB, 0.56 for NBA, 0.75 for NW and −2.21 days for KI. The differences between reciprocal crosses for litter size were of low magnitude and non-significant, which indicate that the maternal effects are not important between these lines. In general, the lines did not show significant differences in direct and maternal genetic effects for TB, NBA and NW but there were some significant differences for KI, which ranged from 1.54 to 6.85 days in direct effects and from 0.63 to 3.38 days for maternal effects. A positive and, in some cases, relevant heterosis was found. The largest heterosis was for TB in the HV cross (1.05 rabbits), followed by the AH (0.74 rabbits), AV (0.57 rabbits) and LH (0.55 rabbits) crosses. For NBA, significant heterosis was found in HV (1.11 rabbits) and AV (0.49 rabbits) and for NW in AV (0.90 rabbits), LH (0.70 rabbits) and LV (0.58 rabbits). Favourable and significant heterosis for KI was found in AV and LV crosses, whereas it was unfavourable in AL and in LH. The more recommended crosses were AV and LH, showing the greatest performances on NW, while the cross HV, which shows the greatest performances an NBA, could be highly recommended when cross-fostering is practised to equalise litter sizes after birth, in this situation the lower NW performance observed could be improved.